Stakeholders Approach in Halal Tourism Development Strategy: A Case Study in Ponorogo District - Muhammad Ridlo Zarkasyi; Dhika Amalia Kurniawan; Fajar Surya Ari Anggara (Universitas Muhammadiyah Ponorogo, 2022)
The contribution of Muslim-friendly tourist sector, or halal tourism, towards the growth of economy have been significantly increasing for the past five years. Indonesia occupies the top five of outbound Muslim Travel Countries. This country has natural resources and cultures that are related to Islamic world thus it is ready to turn into halal tourism destination. However, there is still a gap in understanding of halal tourism that some parties deny to carry halal tourism theme in various province nor areas in Indonesia. Hence, there is no good awareness of halal tourism in Indonesian society. Therefore, a strategy to develop halal tourism in Indonesia is enormously needed. This study aims to arrange a strategy in halal tourism development using stakeholder approach. This was a descriptive qualitative study that the data collection technique used primary data through focus group discussion with 30 speakers consisting of stakeholders; government, Department of Tourism and Culture, academicians, media, tourism business sector, and the societies. The results showed that Governments need to have clear concepts, indicators, and rule related to halal tourism. They also needed to build awareness to the relevant stakeholders of halal tourism concept. It was then followed by the tourism business sector that needed to get empowerment in a sustainable program to inform them about halal tourism concept. To academician, they could participate in researches about various strategies to develop halal tourism and collaborate in training, mentoring, and monitoring the implementation of halal tourism by tourism business sector and other stakeholders. The tourists also required to get education related to the importance of halal tourism thus they could promote, give testimonial experience about halal travel, appreciate the halal tourism, and went viral for it. Moreover, the societies needed to be empowered in increasing the tourism potentials around them, as well as given opportunities to collaborate with tourism business sector, and synergize with the other stakeholders. As for the media or press, they needed to be more active in promoting, giving information related to the existence of halal tourism in Ponorogo district since the help of the media brought positive impacts to gain the attentions of not only local travelers but also overseas tourists to visit Ponorogo tourism objects.